X‐ray reflectivity method for the characterization of InGaN/GaN quantum well interface. Issue 8 (6th January 2017) - Massabuau, Fabien; Piot, Nicolas; Frentrup, Martin; Wang, Xiuze; Avenas, Quentin; Kappers, Menno; Humphreys, Colin; Oliver, Rachel
Abstract: A method to characterize the interface of InGaN/GaN quantum wells by X‐ray reflectivity is presented. The interface roughness can be obtained from the ratio of diffuse to specular scatterings obtained on a transverse ω ‐scan. Rotation around the azimuthal φ angle allows for information about the directionality of the roughening mechanisms to be obtained. The method allows for quick identification of the presence or absence of gross well width fluctuations in the quantum well, providing that the interface is chemically sharp. When the interface exhibits chemical grading, compositional fluctuations across the terraced structure of the quantum well surface lead to aggravated roughness as the barrier is grown, which may be misinterpreted as gross well width fluctuations. This method carries promises for complementing analysis by transmission electron microscopy as it is non‐destructive, fast, and allows multi‐directional characterization of the roughness. It would therefore be particularly useful to detect process deviation in a production line, where prior knowledge of the sample is already available.